An age-structured two-strain epidemic modelwith super-infection - Xue-Zhi Li; Ji-Xuan Liu; Maia Martcheva (Mathematical Biosciences and Engineering)
This articlefocuses on the study of an age-structuredtwo-strain model with super-infection. The explicit expression ofbasic reproduction numbers and the invasion reproduction numberscorresponding to strain one and strain two are obtained. It isshown that the infection-free steady state is globally stable ifthe basic reproductive number $ R_0 $ is below one. Existenceof strain one and strain two exclusive equilibria is established.Conditions for local stability or instability of the exclusive equilibria of thestrain one and strain two are established. Existence ofcoexistence equilibrium is also obtained under the condition that bothinvasion reproduction numbers are larger than one.